HUBUNGAN PEMBERIAN ASI (AIR SUSU IBU) TERHADAP PERTUMBUHANANAK USIA 1-3 TAHUN DI WILAYAH KERJA PUSKESMAS BULELENG I - kadek ayu suarmini; Indrie Lutfiana; Semi .; Desi Fitriani; Sri Suryati (MIDWINERSLION : Jurnal Kesehatan STIKes Buleleng, 2020)
The growth and development of children of Todler's age is largely determined by the amount of breast milk obtained, including energy and other nutrients contained in the milk. ASI has various benefits that are good for the growth and development of children and can also reduce the risk of acute and chronic diseases (Chris Suhud, 2013). Where mother's milk (ASI) is the best food that is needed by children to grow and develop. (MOH, 2010). The purpose of this study is to determine the relationship of giving breastmilk ASI to the growth of children aged 1-3 years in the work area of ​​Sukasada I health center.The design of this study uses the research design used in this study is observational with a case control approach. The sample in this study were 38 respondents. The independent variable is the provision of breastfeeding and the dependent variable is the growth of children aged 1-3 years. The data in this study was taken by filling out the questionnaire.Judging from the results of the bivariate analysis using chi square it was found that the value of p 0,000. This result is significant with a p value of less than 0.05, so the hypothesis is answered that there is a relationship between the duration of breastfeeding and the growth of children aged 1-3 years in the Puskesmas Sukasada I. Giving ASI is an important factor for the growth of children. ASI is a nutritional intake that is in accordance with the needs that will help the growth and development of children. Infants who get enough breast milk means they have good nutrition.